Design and Development of a Scale for Evaluating the Acceptance of Social Robotics for Older People: The Robot Era Inventory - Bevilacqua, Roberta; Di Rosa, Mirko; Riccardi, Giovanni Renato; Pelliccioni, Giuseppe; Lattanzio, Fabrizia; Felici, Elisa; Margaritini, Arianna; Amabili, Giulio; Maranesi, Elvira (Frontiers in Neurorobotics, 2022)
Introduction. Nowadays, there are several robots that have been developed to provide not only companionship to older adults, but also to cooperate with them during health and lifestyle activities. Despite the undeniable wealth of social assistive robotics (SARs), some authors suggest the need to personalize the methods used to deeply understand their acceptance in the real life applications. Methods. Inside the Robot-Era project, a scale was developed to understand the degree of acceptance of the robotic platform. A preliminary test with 21 participants was performed, to assess the statistical validity of the Robot-Era Inventory (REI) scales. Results. Based on the criteria observed in literature, 41 items were developed and grouped in different scales (Perceived robot personality, human-robot interaction, perceived benefit, easiness of use, perceived usefulness). The reliability of the Robot-Era Inventory scale was analyzed with the Cronbach’s alpha, with a mean value 0.79 (range= 0.61-0.91). Furthermore, the results of this pre-test has been compared against a gold standard, the Unified Theory of Acceptance and Use of Technology Model (UTAUT), used in order to test the internal validity of the constructs. Discussion. The Robot-Era Inventory represents a useful tool, that can be easily personalized and included in the assessment of any SARs that cooperate with the older people in real environment applications.